Catcalling Terhadap Supporters Perempuan Persatuan Sepakbola Indonesia Surakarta dalam Analisis Gender - Yuniarti, Sabrina Frisca; Yuhastina, Yuhastina; Rahman, Abdul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Catcalling is one of the gender issues that experience confusion in understanding in society. Catcalling occurs in various spheres of people's lives, one of which is in the field of football, where women are the most likely victims. This study aims to analyze the gender inequality contained in catcalling against Persis female supporters and analyze the role of Persis female supporters in an effort to overcome catcalling. This study uses a qualitative method with a phenomenological approach to describe and analyze the phenomenon of catcalling in in-depth and descriptive gender analysis. The data used are primary and secondary data obtained through interviews and documentation which are then analyzed using Miles & Huberman data analysis techniques. Based on the research conducted, it was found that there was gender inequality in catcalling that occurred to Persis female supporters as victims which were manifested in the form of marginalization, subordination, stereotypes, and violence. Besides that, Persis female supporters perform three roles to overcome gender inequality in catcalling, namely by joining the supporter’s community, following the women supporter’s community, and sharing experiences related to catcalling within the women supporter’s community.